Enhanced degradation of sulfathiazole by electro-Fenton process using a novel carbon nitride modified electrode. (April 2019) - Zhu, Yingshi; Qiu, Shan; Deng, Fengxia; Zheng, Yanshi; Li, Kehong; Ma, Fang; Liang, Dandan
Abstract: A novel carbon nitride graphite-based gas diffusion electrode (g-C3 N4 @GDE) was fabricated and then was used as a cathode in electro-Fenton (EF) to treat sulfathiazole (STZ, a target organic pollutant) at the very first time. The effects of g-C3 N4 doping on electronic properties were explored by Liner scanning voltammetry (LSV), density functional theory (DFT) calculation and rotating disk electrode (RDE). LSV showed an improvement of the electroactive surface area, while DFT calculation showed that the active center increased after N-doping. RDE result indicated that g-C3 N4 @GDE cathode favored 2 electron reduction. Regarding H2 O2 accumulation, g-C3 N4 @GDE reached 2.59 mg h −1 cm −2 and was comparable with the previous investigations. In addition, approximately 100% of STZ degradation coupled with 75.16% total organic carbon (TOC) mineralization could be achieved after 180 min electrolysis under the following conditions: applied current 50 mA, [STZ]0 = 500 mg L −1, [Fe 2+ ] = 100 μM and pH = 3. Moreover, a plausible STZ degradation pathway during EF was proposed based on the detected aromatic intermediates, short-chain carboxylic acids and inorganic ions. Finally, 5 cycles experiments showed that the g-C3 N4 @GDE cathode had a good stability in terms of STZ degradation and TOC mineralization. Graphical abstract: Image 1